POSSIBILITY OF APPLYING CONTEMPORARY ANALYTICAL METHODS IN AUDITING PROCUREMENTS OF AGRICULTURAL COMPANIES - Mihajlovic, Milan; Špiler, Marko; Avakumović, Jelena; Tasić, Svetlana; Vukosavljević, Dejan; Krstić, Snežana (Economics of Agriculture, 2021)
Despite the significant results that State Audit Institution achieved in the domain of determining regularities of doing business and truthfulness of financial reports of budget users, performance audit was given significantly less attention, which points to the necessity of developing a methodology for this discipline, as well as a technique to apply it. This contribution represents an attempt to apply a technique of finding hidden knowledge-implicit knowledge (Data mining – DM) in the process of auditing public procurement procedures and illustrating the significance of developing a technique for assessing the purposefulness of using budget assets on an example of public procurements performed in an agricultural company.